Pelatihan dan Pendampingan Pembuatan Pupuk Organik di Desa Sobo Kecamatan Golewa Barat Kabupaten Ngada - Umbu A Hamakonda; Igniosa Taus; Kristianus Soba; Victoria Coo lea; Victoria Ayu Puspita; Anastasia H P Enga (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The people of Sobo Village mostly live as farmers and ranchers, so the use of livestock manure as organic fertilizer will help reduce the level of environmental pollution. To optimize the utilization of resources in Sobo Village, socialization and training are needed regarding the manufacture of organic fertilizer by utilizing livestock manure. The expected result is a promising opportunity to increase the potential of agriculture and livestock, which in turn will improve the economy of the people of Sobo Village. This activity is carried out through socialization, discussion, and practice. Community service is carried out in four stages: preparation, socialization of organic fertilizer production, and training. Socialization is carried out to inform participants about the process and benefits of organic fertilizer. The practice of making organic fertilizer is an activity of transferring knowledge and technology for processing livestock waste that can be learned and applied by farmers and ranchers. Community service can help farmers and ranchers in Sobo Village make organic fertilizer made from livestock manure. This can be used to meet the fertilizer needs for agricultural crops and marketed to increase the income of farmers and ranchers.